Enigmatic variations: divergent modes of regulating eukaryotic DNA replication. - Kearsey, S; Cotterill, S (2003)
Proteins involved in DNA replication are conserved from yeast to mammals, suggesting that the mechanism was established at an early stage of eukaryotic evolution. In spite of this common origin, recent findings have revealed surprising variations in how replication initiation is controlled, implying that a conserved mechanism has not necessarily resulted in regulatory conservation.